Kemajuan Iptek dan Pembangunan Bangsa Dalam Perspektif Islam - Shahibul Adib (LPPM IAIN Sorong, 2016)
The progress of science and technology not only bring a wide variety of fortune, but also a loss. The advantage is that human power can be replaced by machines. The distance between one place and another can be shortened. The advanced communication tools are created, and so forth. Meanwhile, the disadvantage is that it can produce a product that is very terrible, like germ bombs, chemical bombs, as well as other types of bombs that have devastating explosive power resulted in loss of life and property, and so forth. Islam derived in the earth next to bring the rules or basic principles of ethics, morality and science and technology for the establishment of a high civilization, also teaches that mankind upholds is peaceful and prosperous life, both individual and social nature.